A 56 Year Old Male with Acute Stent Thrombosis During Percutaneous Coronary Intervention, How to Resolve This Problem? - Millisani, Hayla Iqda; Rohman, Mohammad Saifur; Prasetya, Indra; Widito, Sasmojo (Universitas Brawijaya, 2023)
Background: Acute stent thrombosis is the complete occlusion of a coronary artery of the previously implanted stent. This unusual complication occurs in percutaneous coronary intervention (PCI), development of myocardial ischemia, and poor prognosis for the patient. After PCI, acute stent thrombosiscan occur within 0-24 hours and cause the symptoms like acute coronary syndrome. Incidents of stent thrombosis are about 0.6% to 3.4% for Drug Eluting Stent (DES) implantation, depending on the lesion and patient factors. The etiology of acute stent thrombosis is multifactorial, and early detectioncan reduce the mortality rate.Case Illustration: A 56 yo male visited Rumah Sakit Saiful Anwar Malang with stable angina pectoris (Class III symptoms with medical therapy) planned for elective cardiac catheterization with routine medical treatment. During PCI, he complained the chest pain, and from cine angiography evaluation showed no flow at the diagonal branch because of the acute thrombosis. Then got thrombosuction and got a white thrombus. After the PCI procedure, he got fibrinolytic with streptokinase 1.5 million units for 60 minutes. He was transferred to CVCU for observation and discharged after five days.Conclusion: Acute stent thrombosis is a severe complication during and after PCI because it is related to high mortality. The mechanisms by which ST arises are complex and multifactorial and must be early detection.